4-Arylcoumarin inhibits immediate-type allergy - Taechowisan T. (2014)
This study was undertaken to investigate the effect of 4-arylcoumarin (5,7-dimethoxy-4-p-methoxyphenylcoumarin; MPC) on immediate-type allergic reaction and inflammatory cytokine secretion. MPC inhibited compound 48/80-induced systemic reactions in mice. When MPC was given as a pretreatment at concentrations ranging from 0.001 to 1 g/kg, the serum histamine levels induced by compound 48/80 were reduced in a dose-dependent manner. In addition, MPC also inhibited the passive cutaneous anaphylaxis activated by anti-dinitrophenyl (DNP) IgE antibody dose dependently. Furthermore, MPC decreased the phorbol 12-myristate 13-acetate plus calcium ionophore A23187-stimulated tumor necrosis factor-α and interleukin-6 secretion in human mast cells. These results indicate that MPC may be beneficial in the treatment of immediate-type allergic reactions. © 2007 Taylor & Francis.